2008
DOI: 10.1007/s00411-008-0189-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cytogenetic effects of 131I preceded by recombinant human thyrotropin (rhTSH) in peripheral lymphocytes of Wistar rats

Abstract: The present study was carried out to investigate the cytogenetic effects of therapeutic exposure to radioiodine preceded by rhTSH in an animal model. Three groups of Wistar rats (n = 6) were used: one group was treated only with (131)I (11.1 MBq/animal); the other two groups received rhTSH (1.2 mug/rat of either Thyrogen or rhTSH-IPEN, respectively) 24 h before administration of radioiodine. The percentage of lymphocytes with chromosome aberrations and the average number of aberrations and of dicentrics per ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Chromosomal aberrations observed in this study, as well as those found by Silva et al (2008), may be partly a consequence of the combination of 131 I accumulation in the thyroid gland, which acts as an internal source of irradiation, with the concomitant loss of selectivity of damaged bone marrow cells. One possible explanation for this phenomenon is the low penetration energy of b particles, which may only affect a small number of cells but can deposit a fraction of the energy heterogeneously in the nuclei, thereby generating various types of damage in DNA.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Chromosomal aberrations observed in this study, as well as those found by Silva et al (2008), may be partly a consequence of the combination of 131 I accumulation in the thyroid gland, which acts as an internal source of irradiation, with the concomitant loss of selectivity of damaged bone marrow cells. One possible explanation for this phenomenon is the low penetration energy of b particles, which may only affect a small number of cells but can deposit a fraction of the energy heterogeneously in the nuclei, thereby generating various types of damage in DNA.…”
Section: Discussionmentioning
confidence: 81%
“…The study by Silva et al (2008) also had a larger number of chromosomal aberrations in rat lymphocytes after 24 h of treatment with 0.30 mCi of 131 I, with gradual decline after 7 and 30 days. Similar data were reported by Watanabe et al (1998) using the micronucleus cell test with lymphocytes from 25 patients treated with 0.10 Ci of 131 I, in which the micronuclei frequency significantly increased after therapy and decreased after 2 weeks before reaching the baseline.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Several studies have confirmed the mutagenic activity of different doses of 131I based on evidence from the induction of micronuclei [2,3] and the presence of chromosomal aberrations [4,5]. …”
Section: Introductionmentioning
confidence: 99%